See Jane judge: descriptive representation and diffuse support for a State Supreme Court. (8th August 2022) - Lee, Claire; Solberg, Rorie; Waltenburg, Eric N.
ABSTRACT: Women constitute an increasing presence in American political institutions, raising the question: does their growing presence affect attitudes about these institutions' legitimacy? According to descriptive representation, the legitimacy of institutions should increase as institutions diversify. Yet, research finds that descriptive representation's effect is not uniformly positive. Individuals who perceive their group as losing representation profess lower levels of institutional support. We test whether women and men react differently to seeing a woman leading an institution – a State Supreme Court. Using an experiment where subjects were exposed to seeing a woman chief justice, we found that men have lower levels of diffuse support than do men who do not see a woman chief justice. Meanwhile, we find that women with lower levels of education have significantly higher legitimacy scores when they see a woman leading the court.